Hypolipidemic, Antioxidant and Immunomodulatory Effects of Lactobacillus casei ATCC 7469-Fermented Wheat Bran and Spirulina maxima in Rats Fed a High-Fat Diet - Asmaa Abdella; Mohamed F. Elbadawy; Sibel Irmak; Eman S. Alamri (Fermentation, 2022)
Hyperlipidemia is a leading cause of atherosclerosis and coronary heart disease (CHD). This study aimed to investigate the hypolipidemic effect of Lactobacillus casei ATCC 7469-fermented wheat bran extract and Spirulina maxima extract on Sprague–Dawley rats fed a regular or high-fat diet compared to rosuvastatin as a reference drug. Treatment with Lactobacillus casei ATCC 7469-fermented wheat bran and Spirulina maxima resulted in a significant decrease in total cholesterol (TC), triglycerides (TG.), low-density lipoprotein (LDL) and very low-density lipoprotein (VLDL) (p < 0.05) and a significant increase in high-density lipoprotein (HDL) (p < 0.05). That combination also improved liver functions. It also resulted in the improvement of liver oxidative biomarkers and decreased the production of inflammatory markers (TNF-α, IFN-γ, IL-10, and IL-1β). In addition, a significant reduction in inflammation of liver tissues was observed after that treatment. Lactobacilluscasei ATCC 7469-fermented wheat bran extract and Spirulina maxima extract had additive effects on the lipid profile, liver functions and immune system of rats similar to rosuvastatin.